THE ROLE OF ONLINE NEWS CONSUMERS IN LESSENING THE EXTENT OF MISINFORMATION ON SOCIAL MEDIA PLATFORMS (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
This study looks into how people who read news online think about it and helps to reduce the amount of false information spread on social media. The goal of this study was to identify the tactics used by the media when confronted by opposing opinions from their audience in the social media sphere. Social media platforms are essential when people want to debate and get more information on news stories they believe to be false. This study focuses on the importance of a YouTube channel run by a global media outlet that broadcasts a conflicting story. The study used a thematic content qualitative analysis on a sampled comments and used ExportComments.com, a data extraction tool, to extract qualitative data from the YouTube channels. The study revealed that positive comments were followed by positive comments and vice versa. The commenters on these media also frequently search other social media for stories with a similar theme and compare the veracity and coherence of those stories' reported themes. Additionally, these commenters were prepared to defend stories that they believed to be inaccurate and assert that the media should uphold the principle of professionalism. Social media acts as a public sphere. It is not only a political sphere but also a place that is free from private ownership and censorship. The study established that the concept of the public sphere is likely to be abused when the media report conflicting stories that may not auger well with their audience. Although this theory guides the participation of users on the social media platforms, since most are free from the censorship of different players, the media tend to mute the comment sections of their pages for fear of further misinformation and criticism. Social media platforms offer people a reason to speak freely and demonstrate their sentiments openly. The study's results demonstrate that audiences play a significant role in correcting stories on social media, and that constructive journalism is required, with the media needing to play a better role. To cite this article (7th APA style): Ong’ong’a, D. O. (2022). The role of online news consumers in lessening the extent of misinformation on social media platforms? Journal Communication Spectrum: Capturing New Perspectives in Communication 12(2), 96-111. https://doi.org/10.36782/jcs.v12i2.2155